Regulation of FOXM1 by HDAC3 Inhibition Ameliorates Macrophage Endoplasmic Reticulum stress and Apoptosis in Mycobacterium tuberculosis Infection - Jinqi Hao; Lan Zhang; Jiafu Qi; Yanqin Yu (Immunobiology)
Mycobacterium tuberculosis (Mtb) infection may induce significant damage to the host lung tissues. Endoplasmic reticulum stress (ERS) and apoptosis of macrophages are considered key factors affecting the survival and pathogenicity of intracellular Mtb. Forkhead box M1 (FOXM1) is closely implicated in lung diseases. This study aimed to investigate the role of FOXM1 in Mtb infection and the involvement of histone deacetylase 3 (HDAC3) in this process. An in vitro Mtb infection model was established by infecting RAW264.7 macrophages with Mtb H37Ra. The results showed that RAW264.7 macrophages subjected to Mtb infection showed upregulated expressions of ERS markers and FOXM1. FOXM1 overexpression further elevated the levels of ERS and apoptosis markers, pro-inflammatory cytokines, and reactive oxygen species in Mtb-infected macrophages. FOXM1 could bind to the promoter of TXNIP and activate its transcription. Knockdown of TXNIP suppressed the effects of Mtb infection on macrophages, while upregulation of FOXM1 completely abolished the effects of TXNIP knockdown. HDAC3 inhibitor effectively diminished the effects of FOXM1 upregulation on Mtb-infected macrophages. In conclusion, inhibition of HDAC3 may reduce ERS and apoptosis of Mtb-infected macrophages by regulating the FOXM1/TXNIP axis.